2018
DOI: 10.1007/s11682-018-9850-z
|View full text |Cite
|
Sign up to set email alerts
|

Difference in regional neural fluctuations and functional connectivity in Crohn’s disease: a resting-state functional MRI study

Abstract: Patients with Crohn's disease (CD) are shown to have abnormal changes in brain structures. This study aimed to further investigate whether these patients have abnormal brain activities and network connectivity. Sixty patients with CD and 40 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (fMRI) scans. Amplitude of low-frequency fluctuation (ALFF) and seed-based functional connectivity (FC) were used to assess differences in spontaneous regional brain activity and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
(55 reference statements)
5
29
0
Order By: Relevance
“…Altered pre-frontal cortex FC is consistent with previous studies of CD including differences in amplitude of low-frequency fluctuations (29), in regional homogeneity for CD patients without pain (28), and in relation to effective treatment (30). The altered FC between anterior (MPFC) and posterior (LP) nodes within the DMN is also consistent with previous work (29). Although reduced GM volume of MPFC for CD as compared to HC has also been reported (23), this finding was not reproduced in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Altered pre-frontal cortex FC is consistent with previous studies of CD including differences in amplitude of low-frequency fluctuations (29), in regional homogeneity for CD patients without pain (28), and in relation to effective treatment (30). The altered FC between anterior (MPFC) and posterior (LP) nodes within the DMN is also consistent with previous work (29). Although reduced GM volume of MPFC for CD as compared to HC has also been reported (23), this finding was not reproduced in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of brain structure in CD may be in agreement on one result, altered gray matter (GM) of the superior frontal gyrus, although laterality and direction of alteration are inconsistent (22)(23)(24). Studies of brain function in CD have reported numerous FC alterations with very little overlap (25)(26)(27)(28)(29)(30)(31)(32) aside from some agreement on changes in brain networks or regions involved in executive function and/or default mode (26,30,32). Our study aimed to identify brain structural and functional changes in CD as compared to HC.…”
Section: Introductionmentioning
confidence: 97%
“…Their finding suggests a decreased ability to mediate visceral sensation. Building upon the evidence that long‐term inflammation causes alterations in the brain (Kim et al., 2019) and may impact functional results, Bao et al (2018) used other methods, including ALFF and FC, to assess anomalies in the intrinsic activity of the brain after scanning 60 patients with CD. Their study revealed increase in ALFF value in the ACC, further highlighting the role of the ACC in CD symptoms, such as visceral pain.…”
Section: Resultsmentioning
confidence: 99%
“…Although the brain is constrained by the anatomical skeleton, the activities of each node and functional connectivity between any two nodes within these networks are dynamic ( 48 ). By means of spontaneous low-frequency oscillations in the blood oxygenation level-dependent (BOLD) signal, the resting-state functional magnetic resonance imaging (rs-fMRI) has provided a task-free approach which could eliminate some performance-related confoundings and provide a reliable measure of “baseline” brain activity and connectivity ( 49 ). Therefore, with the help of rs-fMRI, this study focused on characterizing how the cognitive-related networks dynamically change to unravel the mechanisms of cognition recovery after rTMS treatment.…”
Section: Discussionmentioning
confidence: 99%